2012
DOI: 10.1186/1471-244x-12-7
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and activities of child and adolescent mental health services in Italy: a regional survey

Abstract: Background: To date, no studies have assessed in detail the characteristics, organisation, and functioning of Child and Adolescent Mental Health Services (CAMHS). This information gap represents a major limitation for researchers and clinicians because most mental disorders have their onset in childhood or adolescence, and effective interventions can therefore represent a major factor in avoiding chronicity. Interventions and mental health care are delivered by and through services, and not by individual, priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…developed from an instrument used in the TRACK study [12], and from other questionnaires found in the literature, at national and international level [16][17][18][19]. The SATMEHT assesses characteristics and policies of CAMHS regarding transition.…”
Section: The Standardized Assessment Tool For Mental Health Transitiomentioning
confidence: 99%
“…developed from an instrument used in the TRACK study [12], and from other questionnaires found in the literature, at national and international level [16][17][18][19]. The SATMEHT assesses characteristics and policies of CAMHS regarding transition.…”
Section: The Standardized Assessment Tool For Mental Health Transitiomentioning
confidence: 99%
“…A substantial proportion of our sample (30 %) received treatment by a GP or by a private child specialist before consulting CAMHS. It seems unlikely that the first consultation with a private specialist was due to a delay of the first visit in the public healthcare sector, causing a diversion to the private health practice, as most units guarantee an initial visit within 2 weeks from the request [ 12 ]. We can only hypothesize that stigma associated with public mental health services could induce parents of children and adolescents with emotional problems initially to seek help elsewhere (i.e., private psychiatrists or psychologists, school counselors, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…CAMHSs are part of the NHS, and their costs are fully covered by the NHS. A detailed description of the clinical interventions delivered by CAMHS, which participated in the study have been reported elsewhere [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…25 One study regarding CAMH in Italy found a significant reduction in access to treatment when CAs received care in the same facilities as adults, since was associated with stigma. 26 Thus, placing CAPS-II i at the center of CAMH care, could help remove the stigma and reduce the institutionalization of children and adolescents, representing a step forward in the care of children and adolescents with mental health pro-blems.…”
Section: Discussionmentioning
confidence: 99%